2017
DOI: 10.1111/nph.14419
|View full text |Cite
|
Sign up to set email alerts
|

Conservation vs divergence in LEAFY and APETALA1 functions between Arabidopsis thaliana and Cardamine hirsuta

Abstract: Summary A conserved genetic toolkit underlies the development of diverse floral forms among angiosperms. However, the degree of conservation vs divergence in the configuration of these gene regulatory networks is less clear. We addressed this question in a parallel genetic study between the closely related species Arabidopsis thaliana and Cardamine hirsuta. We identified leafy (lfy) and apetala1 (ap1) alleles in a mutant screen for floral regulators in C. hirsuta. C. hirsuta lfy mutants showed a complete hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…In the un1 mutants, the genes encoding proteins with high similarity to GIGANTEA 3 (GI3), GIGANTEA-like, Phytochrome A (PHYA), TIME OF CAB EXPRESSION 1 (TOC1), CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), EARLY FLOWERING 3 (ELF3), and Adagio protein 3 (ADO3) were significantly downregulated, while those with high similarity to LATE ELONGATED HYPOCOTYL (LHY) were significantly upregulated. It has been reported that these are key factors in the regulation of the circadian clock and regulate important developmental transitions such as flowering, which was consistent with the involvement of LFY and its orthologs in controlling flowering time and phase transition 3133 .…”
Section: Resultssupporting
confidence: 77%
“…In the un1 mutants, the genes encoding proteins with high similarity to GIGANTEA 3 (GI3), GIGANTEA-like, Phytochrome A (PHYA), TIME OF CAB EXPRESSION 1 (TOC1), CIRCADIAN CLOCK ASSOCIATED 1 (CCA1), EARLY FLOWERING 3 (ELF3), and Adagio protein 3 (ADO3) were significantly downregulated, while those with high similarity to LATE ELONGATED HYPOCOTYL (LHY) were significantly upregulated. It has been reported that these are key factors in the regulation of the circadian clock and regulate important developmental transitions such as flowering, which was consistent with the involvement of LFY and its orthologs in controlling flowering time and phase transition 3133 .…”
Section: Resultssupporting
confidence: 77%
“…This is evidenced by CrLFY activity at the tips of shoots, fronds and pinnae ( Figures 4 – 6 ), all of which develop from one or more apical cells ( Hill, 2001 ; Hou and Hill, 2004 ). Whether fern fronds are homologous to shoots or to leaves in angiosperms is an area of debate ( Tomescu, 2009 ; Vasco et al, 2013 ; Harrison and Morris, 2018 ), but there are angiosperm examples of LFY function in the vegetative SAM ( Ahearn et al, 2001 ; Zhao et al, 2018 ), axillary meristems ( Kanrar et al, 2008 ; Rao et al, 2008 ; Chahtane et al, 2013 ) and in actively dividing regions of compound leaves ( Hofer et al, 1997 ; Molinero-Rosales et al, 1999 ; Champagne et al, 2007 ; Wang et al, 2008 ; Monniaux et al, 2017 ) indicating that a proliferative role in vegetative tissues has been retained in at least some angiosperm species. Consistent with the suggestion that the angiosperm floral meristem represents a modified vegetative meristem ( Theiben et al, 2016 ), the third stage of LFY evolution could have been co-option and adaptation of this proliferation-promoting network into floral meristems, with subsequent restriction to just the flowering role in many species.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that AP1 might be a good candidate to contribute to petal number variation in C. hirsuta , particularly given that ap1 mutants in both C. hirsuta and A. thaliana show variable petal loss ( Bowman et al, 1993 ; Monniaux et al, 2017 ). To test this possibility, we used a genomic construct of A. thaliana AP1 ( AtAP1::AtAP1:GFP ( Urbanus et al, 2009 )), which was sufficient to restore four petals in the ap1 mutant (Mann-Whitney U test, p=1.07e-06) and eliminate the ectopic flowers that characterize the partial loss of floral meristem identity of ap1 mutants (Mann-Whitney U test, p=2.92e-06; Figure 3a–c ).…”
Section: Resultsmentioning
confidence: 99%
“…This translational fusion contains a 6.6 kb genomic fragment of A. thaliana AP1 including 3 kb of regulatory sequence upstream of the translational start. ChAP1::ChAP1:GFP was previously described ( Monniaux et al, 2017 ) and contains a comparable 6.6 kb genomic fragment of C. hirsuta AP1 . Ten independent lines of ChAP1::ChAP1:GFP were generated in C. hirsuta wild type and A. thaliana ap1-12 .…”
Section: Methodsmentioning
confidence: 99%